Back Cover: Size‐ and Orientation‐Selective Encapsulation of C70 by Cycloparaphenylenes (Chem. Eur. J. 42/2013). Issue 42 (7th October 2013) - Iwamoto, Takahiro; Watanabe, Yoshiki; Takaya, Hikaru; Haino, Takeharu; Yasuda, Nobuhiro; Yamago, Shigeru
<x xml:space="preserve">Abstract</x> The shortest possible C70 peapods were formed in a size‐ and orientation‐selective manner from C70 and either [10]cycloparaphenylene (CPP) or [11]CPP as 1:1 complexes. C70 exists in two distinct orientations inside the CPP cavity, namely "lying" and "standing", depending on the size of the CPP. The interaction between [10]CPP and the short axis of C70 is isotropic, but that between [11]CPP and C70 is anisotropic, involving the radial deformation of [11]CPP to an ellipsoidal shape. This "induced‐fit" occurred due to the radically elastic character of the CPPs and maximized the van der Waals interactions with the long axis of C70. For more details, see the Full Paper by S. Yamago et al. on page 14061 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>